Validasi Metode HPLC untuk Penetapan Aspirin dan Asam Salisilat dalam Plasma Kelinci (Lepus curpaeums) secara Simultan - Siswanto, Agus; Fudholi, Achmad; Nugroho, Akhmad Kharis; Martono, Sudibyo (Jurnal Kefarmasian Indonesia, 2016)
Aspirin is a nonsteroidal anti-inflammatory drug which also has the effect of antiplatelet for stroke prevention. Aspirin inside human body is very easy to break down into salicylic acid as the main metabolite. The aim of this study is to develop and validate the method for determinating aspirin and salicylic acid concentration in plasma by HPLC. Method validation including system suitability test, linearity test, determination of LOD and LOQ, recovery, accuracy and precision. Concentration of analytes in blood is measured by HPLC using benzoic acid as internal standard, with condition Purospher column Endcapped Star RP-18 (250 x 4.6 mm id, 5 m), acetonitrile : buffer phosphate 20 mM pH 2.5 (30:70 v/v) as mobile phase, injection volume 20 mL, flow rate 1.5 mL/minute, and UVVis detector λ 230 nm. The results showed that the proposed method meets the requirements of system suitability and good linearity (r > 0,990) with LOQ (aspirin = 0.024 mg/mL, salicylic acid = 0.336 mg/mL) and LOD (aspirin = 0.007 mg/mL, salicylic acid = 0.101 mg/mL). The method of analysis provides recovery of 85-115 %, accuracy and precision in accordance with the requirements for bioanalytical with CV < 5 %. Therefore, the proposed method is applicable to determine of aspirin and salicylic acid concentration in plasma.